Trajetórias dos alunos da Educação de Jovens e Adultos em Minas Gerais, 2007-2017 - Leandro Alves Felício (2022)
Little is known about the trajectories of those who changed from regular education to Youth and Adult Education (EJA). Thus, through exploratory analysis, this thesis aims at investigating the composition by sex and age of students who made such a change, in the Brazilian state of Minas Gerais, from 2007 to 2017. This work assumes that demographic changes have provided the state of Minas Gerais with a favorable demographic moment, also known as “Window of Opportunities”, which is parallel and directly related to improvements in educational indicators. However, even in a demographically favorable scenario, there are still low levels of schooling and high educational inequality. In this context, EJA becomes a way of equalizing opportunities and repairing educational inequalities. In order to understand why EJA is offered, a brief history of its standardization and systematization is presented; and to understand the demand for this modality, data on school attendance rate, illiteracy rate, age-grade distortion and school flow is also provided. Finally, there is an exploratory analysis on some sociodemographic characteristics of students who switched from regular education to EJA. The results indicate trajectories marked by grade retention; early switching to EJA, both related to age and age-grade distortion; gender discrepancy; and also, a considerable rate of spatial mobility.